Penyuluhan Standarisasi Lampu Penerangan Jalan Umum Bagi Masyarakat Desa Manggihan Kecamatan Getasan Kabupaten Semarang - Eka Nuryanto Budisusila; Dedi Nugroho; Muhammad Khosyi'in (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Public Street Lighting (PSL) plays an important role in improving safety, security, and comfort for communities during nighttime activities. However, in many rural areas, as is the case in Manggihan Village, PSL installations at several points are installed haphazardly with irregular pole spacing, without paying attention to proper technical and safety factors, and are simply able to be turned on only. This community service program aims to improve public understanding of street lighting installation standards based on Indonesian National Standards and electrical installation regulations. The implementation method included educational counseling, discussions, and technical assistance for residents of Manggihan Village, Getasan District, Semarang Regency. The materials delivered covered the basic concepts of street lighting systems, illumination standards, energy-efficient lighting technology, and safe electrical installation practices. The results showed an improvement in community knowledge regarding proper installation standards for street lighting systems. The activity also increased awareness of energy-efficient LED lighting and safe electrical practices. This program is expected to support the development of safer and more efficient rural street lighting infrastructure.